Comparitive Efficacy of Topical Adapalene Plusoral Azithromycin Versus Topical Adapalene Plus Oral Doxycycline in Treatment of Acne Vulgaris - Muzaffar, Bushra; Shaikh, Zafar Iqbal; Malik, Sadia (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare the efficacy of topical Adapalene plus oral Azithromycin versus topical Adapalene plus oral Doxycycline in treating mild to moderate acne vulgaris. Study Design: Quasi-experimental study. Place and Duration of Study: Dermatology Department, Pak Emirates Military Hospital Rawalpindi, from Jun to Dec 2017. Methodology: A total of 60 patients were enrolled in the study and were grouped into two groups, A and B, comprising 30 patients in each group. Random tables were used to allocate patients to each group. In this study, Group A was prescribed topical Adapalene be applied as a thin layer over affected areas at night plus oral Azithromycin 250 mg capsule once daily for 03 months, while Group B was given the same instructions for topical Adapalene plus oral Doxycycline100 mg twice daily for 03 months. Fifty percent reduction of lesions from the baseline was considered an effective therapeutic response. Results: In our patient sample mean age in Group A was 18 years (± 4.77), while the mean age in Group B was 19 years (± 5.12). In Group A, 13 (43%) patients were male, and 17 (57%) patients were female, while in Group B, 12 (40%) patients were male, and 18 (60%) patients were female. Treatment in Group A was effective in 90% of patients, while 73% of patients in Group B showed effective response. Conclusion: This study concluded that combination of topical Adapalene plus oral Azithromycin was equally efficacious to topical Adapalene plus oral Doxycycline in treating mild and moderate acne vulgaris.